The Relationship between School Administrators’ Management Behaviors and Teachers’ Work Motivation in Schools the Secondary Educational Service Area Office Phra Nakhon Si Ayutthaya - ภักดี ศศิวิมล; กลิ่นเกษร อุษาพร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to: 1) examine the level of administrative behaviors of school administrators; 2) investigate the level of teachers’ work motivation; and 3) examine the relationship between the administrative behaviors of school administrators and the work motivation of teachers under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office. The sample used in this research consisted of 308 teachers under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office in the 2025 academic year. The sample size was determined using the table of Yamane (1973). Stratified random sampling was employed, using school size as the sampling unit, followed by simple random sampling through a lottery method. The research instrument was a five-point rating scale questionnaire. The Index of Item-Objective Congruence (IOC) ranged from 0.80 to 1.00, and the reliability coefficient was .984. The statistics used for data analysis included frequency, percentage, mean, and standard deviation. The relationship between variables was analyzed using the Pearson Product–Moment Correlation Coefficient. The findings revealed that: • The administrative behaviors of school administrators under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office were at a high level overall, and each aspect was also at a high level. • Teachers’ work motivation under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office was at the highest level overall, with each aspect ranging from high to highest levels. • The relationship between the administrative behaviors of school administrators and teachers’ work motivation in schools under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office showed a positive relationship at a high level, with a correlation coefficient of .831, which was statistically significant at the .01 level.